Measuring brand equity in football clubs: the case of Reggiana Calcio 1919 - Tambè, Giuseppe (2021)
This Study presents a marketing and statistical analysis that focuses on the measurement of the brand equity of Reggiana Calcio 1919, an Italian second division football club that has recently been promoted to the second division, namely, Serie B. Reggiana Calcio 1919 was selected as the target club in this research project because in the literature there are limited studies on small sports organisations. The main aim of this study is to analyse the most significant determinants of brand equity of the club and how both its fanbase and customers perceive the brand. Reggiana Calcio 1919 is a historic Italian football club, although it does not have a victorious past. For the purpose of the research project, a quantitative research approach was followed by using IMB SPSS software along with being a qualitative approach as primary and secondary data. The data collected was applied to the Keller Customer-Based Brand Equity model (CBBE), based on its four main dimensions: Brand Awareness, Brand Response, Brand Meaning and Brand Loyalty. The results have identified that Reggiana Calcio 1919 strongly position its brand at a regional level, the club has a well-established engagement with its fanbase and customers who are intensely loyal and identify themselves with the brand. However, the club lack of investments on football facilities which, in turn, subtracts potential market value as these investments would benefit the club not only financially but also in terms of image as it would appear as a strongly reliable brand. The research is significant to understand what makes a small football club competitive within modern football industry.